European Green Capital: environmental urbanism, or an addition to the entrepreneurial toolbox?. Issue 4 (June 2020) - Nurse, Alexander; North, Peter
Abstract : Since 2010, cities across Europe have served as 'European Green Capital' (EGC), an initiative celebrating the contribution of environmental action to urban life. Drawing together the experiences of initial EGC winners, for the first time this paper considers what EGC means to city managers as a way of celebrating and driving forward environmental performance, as well as promoting their own cities. Through a discussion of the experiences of the initial host cities, the paper outlines a typology of EGCs. In doing so the paper notes a shift to a harder-edged economic outlook, which increasingly incorporates themes of entrepreneurial economic growth and competitiveness.